NP0 ceramic dielectric material and preparation method thereof

By adopting the combination of BLT phase powder and CNT phase powder, combined with the use of modification additives and sintering aids, the problem that existing NP0 type ceramic materials are difficult to have high dielectric constant and low dielectric loss, and the combination of high dielectric constant and low dielectric loss is achieved, which is suitable for a variety of electronic devices.

CN119661216AActive Publication Date: 2025-03-21HANGZHOU XINGRONG TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510193287.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-21
Publication Date
2025-03-21
Estimated Expiration
2045-02-21

AI Technical Summary

Technical Problem

It is difficult for existing NP0 ceramic materials to have both high dielectric constant and low dielectric loss.

Method used

Using a combination of BLT phase powder and CNT phase powder, a mixed powder is prepared by wet planetary grinding, and a modified additive and sintering agent are added. After drying, screening, granulation, cold isostatic molding and sintering, NP0 ceramic dielectric material with high dielectric constant and low dielectric loss is prepared.

Benefits of technology

It realizes both high dielectric constant and low dielectric loss of NP0 ceramic dielectric materials, and is suitable for high-frequency circuits, wireless communications, microwave devices and capacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661216A_ABST
    Figure CN119661216A_ABST
Patent Text Reader

Abstract

The invention relates to an NP0 ceramic dielectric material and a preparation method thereof. The NP0 ceramic dielectric material is prepared from the following raw materials: BLT phase powder, CNT phase powder, a modified additive and a sintering aid. The NP0 ceramic dielectric material provided by the invention is a ceramic dielectric material with high dielectric constant and low dielectric loss.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to ceramic dielectric materials used in the fields of electronic devices, communication systems, capacitors, etc., and in particular to an NPO ceramic dielectric material and a preparation method thereof. Background Art

[0002] With the continuous development of modern electronic technology, the demand for high-performance ceramic dielectric materials is increasing, especially for materials with high dielectric constant and low dielectric loss. NP0 ceramics have been widely used in high-frequency circuits, wireless communications, microwave devices and capacitors due to their excellent temperature characteristics and relatively stable electrical properties. NP0 ceramics usually exhibit a temperature coefficient characteristic close to zero, that is, their dielectric constant changes very little with temperature, which is suitable for high-performance electronic applications that require temperature stability.

[0003] However, existing NP0 ceramic materials still face some challenges, especially in the balance between dielectric constant and dielectric loss. At present, there are few NP0 ceramic materials on the market that have both high dielectric constant and low dielectric loss. For example, the domestic invention patent CN102690118A proposes an NP0 ceramic material based on BRT as the main phase, ZnB as a sintering aid, and BiTi as the second phase. The dielectric loss of this material at room temperature is less than 0.05%, but its dielectric constant is relatively low, ranging from 45-70, which is difficult to meet the demand for high dielectric constant materials. In addition, the domestic invention patent CN110483034A proposes a high dielectric constant NP0 ceramic material, using Although the system has the advantage of a high dielectric constant, according to common knowledge in the art, the dielectric loss of the system is usually high.

[0004] In view of the defects of the prior art, developing a new type of NP0-type ceramic dielectric material with high dielectric constant and low dielectric loss is an urgent problem to be solved by technical personnel in this field, and it has broad application prospects. Summary of the invention

[0005] The present invention aims to solve the problem that it is difficult to have both high dielectric constant and low dielectric loss in existing NPO ceramic dielectric materials. The present invention provides an NPO ceramic dielectric material and a preparation method thereof. The NPO ceramic dielectric material provided by the present invention has the advantages of both high dielectric constant and low dielectric loss.

[0006] The present invention provides an NP0 ceramic dielectric material, which is made of the following raw materials: BLT phase powder, CNT phase powder, modification additives and sintering aids, wherein the chemical formula of the BLT phase powder is (Bi 0.9 La 0.1 ) 2 Ti 2 O7 ; The chemical formula of the CNT phase powder is Ca 0.6 Nd 0.8 / 3 TiO 3 .

[0007] In the present invention, the BLT phase powder is prepared by the following method: bismuth oxide (Bi 2 O 3 ), titanium dioxide (TiO 2 ) and lanthanum oxide (La 2 O 3 )According to (Bi 0.9 La 0.1 ) 2 Ti 2 O 7 The ingredients are weighed in a stoichiometric ratio, and are ground into fine powder by wet planetary ball milling. The fine powder is then sintered at 900-1100°C to form a BLT phase powder.

[0008] In the present invention, the CNT phase powder is prepared by the following method: calcium carbonate (CaCO 3 ), titanium dioxide (TiO 2 ) and neodymium oxide (Nd 2 O 3 ) According to Ca 0.6 Nd 0.8 / 3 TiO 3 The ingredients are weighed and mixed in a stoichiometric ratio, and then the fine powder is sintered at 1000-1200°C to form a CNT phase powder.

[0009] In the present invention, the weight ratio of the BLT phase powder to the CNT phase powder is 3:7, 4:6, 5:5, 6:4 or 7:3; preferably 4:6, 5:5, 6:4 or 7:3; more preferably 5:5, 6:4 or 7:3; optimally 6:4.

[0010] In the present invention, the modifying additive is niobium pentoxide (Nb 2 O 5 ) and zirconium oxide (ZrO 2 )

[0011] In the present invention, in the modifying additive, niobium pentoxide (Nb 2 O 5 ) and zirconium oxide (ZrO 2 )’s weight ratio is 1:3.

[0012] In the present invention, the sintering aid is boron oxide (B 2 O 3 ) and aluminum oxide (Al 2 O 3)

[0013] In the present invention, in the sintering aid, the boron oxide (B 2 O 3 ) and aluminum oxide (Al 2 O 3 ) by weight ratio is 2:1.

[0014] In the present invention, the raw material further includes a binder, and the binder is polyvinyl alcohol (PVA).

[0015] The present invention also provides a method for preparing an NP0 ceramic dielectric material, which comprises the following steps: (1) mixing BLT phase powder and CNT phase powder in a weight ratio of 1:(0.4-2.5), and adding a modifying additive and a sintering aid to obtain a mixed powder.

[0016] (2) The mixed powder is then passed through a wet planetary ball mill, and the milled slurry is then dried and passed through a 100-mesh sieve.

[0017] (3) Adding 0.5-2.5% by mass of polyvinyl alcohol to the mixed powder passing through a 100-mesh sieve to granulate the mixed powder, and then forming the mixed powder into a blank by cold isostatic pressing, and then sintering the blank at 950-1200° C. to prepare the NP0 ceramic dielectric material.

[0018] The BLT phase powder, the CNT phase powder, the modifying additive and the sintering aid are all as defined above.

[0019] In the present invention, BLT phase powder and CNT phase powder are weighed and mixed according to a weight ratio of 3:7, 4:6, 5:5, 6:4 or 7:3; preferably 4:6, 5:5, 6:4 or 7:3; more preferably 5:5, 6:4 or 7:3; and most preferably 6:4.

[0020] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0021] The reagents and raw materials used in the present invention are commercially available.

[0022] The positive progressive effect of the present invention is that the present invention obtains a high dielectric constant and low dielectric loss NP0 ceramic dielectric material. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a scanning electron microscope photograph of NP0 ceramic dielectric material 1, showing the surface morphology of the material after sintering.

[0024] Figure 2 This is a scanning electron microscope photograph of NP0 ceramic dielectric material 2, showing the surface morphology of the material after sintering.

[0025] Figure 3 This is a scanning electron microscope photograph of NP0 ceramic dielectric material 3, showing the surface morphology of the material after sintering.

[0026] Figure 4 This is a scanning electron microscope photograph of NP0 ceramic dielectric material 4, showing the surface morphology of the material after sintering.

[0027] Figure 5 This is a scanning electron microscope photograph of NP0 ceramic dielectric material 5, showing the surface morphology of the material after sintering. DETAILED DESCRIPTION

[0028] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0029] Example 1: Preparation of BLT phase powder: The raw material bismuth oxide (Bi 2 O 3 ), titanium dioxide (TiO 2 ) and lanthanum oxide (La 2 O 3 )According to the stoichiometric ratio (Bi 0.9 La 0.1 ) 2 Ti 2 O 7 Weigh the ingredients and use a wet planetary ball mill. The ball mill is made of nylon, the grinding body is a zirconium oxide ball, the ball medium is anhydrous ethanol, the weight ratio of the material, zirconium ball, and ethanol is 1:1:0.8, the ball speed is 200 r / min, and the duration is 4 hours. The slurry after ball milling is dried in an electric blast oven at 80°C, and after drying, it is passed through a 100-mesh sieve. The sieved powder is calcined at 950°C for 4 hours to obtain BLT phase powder.

[0030] Preparation of CNT phase powder: The raw material calcium carbonate (CaCO 3 ), titanium dioxide (TiO 2 ) and neodymium oxide (Nd 2 O 3 ) According to the stoichiometric ratio of Ca 0.6 Nd 0.8 / 3 TiO 3Weigh the ingredients and use a wet planetary ball mill. The ball mill is made of nylon, the grinding body is a zirconium oxide ball, the ball medium is anhydrous ethanol, the weight ratio of the material, zirconium ball, and ethanol is 1:1:0.8, the ball speed is 200 r / min, and the duration is 4 hours. The slurry after ball milling is dried in an electric blast oven at 80°C, and after drying, it is passed through a 100-mesh sieve. The sieved powder is calcined at 1100°C for 4 hours to obtain the final CNT phase powder.

[0031] The total weight of 30 grams of BLT phase powder and CNT powder were mixed in a weight ratio of 3:7, and the modified additive niobium pentoxide (Nb 2 O 5 ) 0.5 g, zirconium oxide (ZrO 2 ) 1.5 g, sintering agent boron oxide (B 2 O 3 ) 1.2 g, aluminum oxide (Al 2 O 3 ) 0.6 g to obtain a mixed powder. The mixed powder was ball-milled for the second time using a wet planetary ball mill. The ball-milling medium was deionized water. The weight ratio of the material, zirconium ball, and deionized water was 1:1:0.8. The ball-milling speed was 200 r / min and the ball-milling time was 12 hours. The slurry after ball milling was dried in an 80°C electric blast oven and passed through a 100-mesh sieve.

[0032] Polyvinyl alcohol (PVA) with a mass fraction of 2% was added to the mixed powder passing through a 100-mesh sieve for granulation; then, cold isostatic pressing was performed at a pressure of 180 MPa to form a disc-shaped green body with a diameter of about 20 mm and a thickness of about 1 mm.

[0033] The disc-shaped green body was sintered at 1100°C for 3 hours. The heating rate was 2°C / min, and the temperature was kept at 550°C for 3 hours for debinding. Finally, the NP0 ceramic dielectric material 1 was obtained. The scanning electron microscope photo of the NP0 ceramic dielectric material 1 after sintering is shown in FIG. Figure 1 shown.

[0034] Example 2: The preparation method of Example 2 is basically the same as that of Example 1, the main difference being that 30 grams of BLT phase powder and CNT phase powder are mixed in a weight ratio of 4 to 6; finally, NP0 ceramic dielectric material 2 is obtained. The scanning electron microscope photo of NP0 ceramic dielectric material 2 after sintering is shown in FIG. Figure 2 shown.

[0035] Example 3: The preparation method of Example 3 is basically the same as that of Example 1, the main difference being that 30 grams of BLT phase powder and CNT phase powder are mixed in a weight ratio of 1:1; finally, NP0 ceramic dielectric material 3 is obtained. The scanning electron microscope photo of NP0 ceramic dielectric material 3 after sintering is shown in FIG. Figure 3 shown.

[0036] Example 4: The preparation method of Example 4 is basically the same as that of Example 1, the main difference being that 30 grams of BLT phase powder and CNT phase powder are mixed in a weight ratio of 6 to 4; finally, NP0 ceramic dielectric material 4 is obtained. The scanning electron microscope photo of NP0 ceramic dielectric material 4 after sintering is shown in FIG. Figure 4 shown.

[0037] Example 5: The preparation method of Example 5 is basically the same as that of Example 1, the main difference being that 30 grams of BLT phase powder and CNT phase powder are mixed in a weight ratio of 7 to 3; finally, NP0 ceramic dielectric material 5 is obtained. The scanning electron microscope photo of the sintered NP0 ceramic dielectric material is shown in FIG. Figure 5 shown.

[0038] Effect Example 1: The ceramic materials obtained in the above five examples are metallized for dielectric performance testing. The method is to apply a silver-containing slurry to the upper and lower surfaces of the ceramic disc sample by coating, and then dry and sinter at high temperature to form a conductive silver electrode to prepare a disc capacitor. The following room temperature dielectric constant, room temperature dielectric loss and dielectric constant temperature change rate are tested by the capacitance method.

[0039] (1) Dielectric constant at room temperature (ε r ) Test: Test instrument: Agilent E4980A precision LCR AC impedance tester.

[0040] Test conditions: frequency 1kHz, test environment temperature 25°C, humidity 50%.

[0041] The calculation formula is ε r = (C×d) / (S×ε 0 ), where C is the measured capacitance of the ceramic capacitor; d is the thickness of the ceramic dielectric along the electric field direction; S is the area of ​​the ceramic capacitor plate; ε 0 is the dielectric constant of vacuum, which is 8.85×10 -12 F / m.

[0042] (2) Room temperature dielectric loss (tanδ) test: The dielectric loss of the material is tested at a frequency of 1 kHz using an Agilent E4980A precision LCR AC impedance tester, the same as the dielectric constant.

[0043] (3) Temperature-dependent capacitance change (TCC) test: The test sample is placed in a temperature-controlled environment, and the dielectric constant value is measured every 10°C in the temperature range from -50°C to 150°C using an Agilent E4980A precision LCR AC impedance tester. The experiment is conducted in a temperature-controlled furnace (temperature adjustment accuracy ±1°C).

[0044] Calculate the temperature change rate (TCC) of the dielectric constant within the temperature range. The calculation formula is TCC = (10 6 ×(ε (T) -ε (25°C) )) / ((T-25)×ε (25°C) ). Where T is the test temperature, ε (T) is the dielectric constant at the test temperature, ε (25°C) is the dielectric constant at 25°C.

[0045]

[0046] According to the data in Table 1, the room temperature dielectric constant of each sample ranges from 45 to 155. The room temperature dielectric constant increases with the increase of BLT content. When the BLT / CNT ratio is 6:4 (Example 4), it reaches a maximum value of 155, which has high room temperature dielectric properties. However, when the ratio continues to increase to 7:3, the room temperature dielectric constant decreases slightly, but still maintains a high level.

[0047] The room temperature dielectric loss of each sample ranges from 0.194 to 0.040, and is generally in the lower dielectric loss range. As the BLT content increases, the dielectric loss gradually decreases, and the lowest value is 0.040 in Example 4 (ratio 6:4), indicating that the material with this ratio has the lowest energy loss in practical applications.

[0048] The capacitance-temperature change rate of the sample in Example 1 is positive 13.2 ppm / °C, indicating that the capacitance value increases with increasing temperature. In other examples, the capacitance-temperature change rates are all negative, and the absolute value gradually decreases as the BLT content increases. The best is Example 4, with a capacitance-temperature change rate of -2.1 ppm / °C, indicating that the sample obtained by this ratio has the best stability and is suitable for use in environments with large temperature fluctuations.

[0049] Further analysis of the surface morphology differences revealed Figure 1-Figure 5 From the scanning electron microscope images of the samples of Examples 1-5 shown in , it can be seen that the surface of the sample of Example 4 is the most dense and flat during sintering.

[0050] In summary, the ceramic dielectric material obtained in Example 4 has excellent NP0 performance and has the characteristics of high dielectric constant and low dielectric loss.

Claims

1. An NP0 ceramic dielectric material, characterized in that: The invention is made of the following raw materials: BLT phase powder, CNT phase powder, modification additive and sintering aid, wherein the chemical formula of the BLT phase powder is (Bi 0.9 La 0.1 )2Ti2O7; the chemical formula of the CNT phase powder is Ca 0.6 Nd 0.8 / 3 TiO3.

2. The NP0 ceramic dielectric material according to claim 1, characterized in that The BLT phase powder is prepared by the following method: bismuth oxide, titanium dioxide and lanthanum oxide are mixed according to (Bi 0.9 La 0.1 )2Ti2O7 are weighed and mixed in a stoichiometric ratio, and the mixture is formed into a fine powder by wet planetary ball milling, and then the fine powder is sintered at 900-1100°C to form a BLT phase powder.

3. The NP0 ceramic dielectric material according to claim 1, characterized in that The CNT phase powder is prepared by the following method: calcium carbonate, titanium dioxide and neodymium oxide are mixed according to Ca 0.6 Nd 0.8 / 3 TiO3 is weighed and mixed in a stoichiometric ratio, and is made into fine powder by wet planetary ball milling, and then the fine powder is sintered at 1000-1200°C to form CNT phase powder.

4. The NPO ceramic dielectric material according to claim 1, characterized in that The modifying additive is one or more of niobium pentoxide and zirconium oxide.

5. The NPO ceramic dielectric material according to claim 1, characterized in that The sintering aid is one or more of boron oxide and aluminum oxide.

6. The NPO ceramic dielectric material according to claim 5, characterized in that The sintering aids are boron oxide and aluminum oxide, wherein the weight ratio of the boron oxide to the aluminum oxide is 2:

1.

7. The NPO ceramic dielectric material according to claim 4, characterized in that: The modifying additives are niobium pentoxide and zirconium oxide, wherein the weight ratio of the niobium pentoxide to the zirconium oxide is 1:

3.

8. The NPO ceramic dielectric material according to claim 1, characterized in that The weight ratio of the BLT phase powder to the CNT phase powder is 5:5, 6:4 or 7:

3.

9. A method for preparing an NP0 ceramic dielectric material, characterized in that: The method comprises the following steps: (1) mixing BLT phase powder and CNT phase powder in a weight ratio of 1:(0.4-2.5), and adding a modifying additive and a sintering aid to obtain a mixed powder; (2) then subjecting the mixed powder to a wet planetary ball mill, and then drying the milled slurry and passing it through a 100-mesh sieve; (3) adding 0.5-2.5% by mass of polyvinyl alcohol to the mixed powder passing through the 100-mesh sieve for granulation, and then forming a blank by cold isostatic pressing, and then sintering the blank at 950-1200° C. to prepare the NP0 ceramic dielectric material; wherein the BLT phase powder is as defined in claim 2; the CNT phase powder is as defined in claim 3; the modifying additive is as defined in claim 4; and the sintering aid is as defined in claim 5.

10. The method for preparing the NPO ceramic dielectric material according to claim 9, characterized in that: In step (1), the weight ratio of BLT phase powder to CNT phase powder is 5:5, 6:4 or 7:3.

Citation Information

Patent Citations

  • NP0 type ceramic capacitor dielectric material and its preparation method

    CN102690118A

  • NP0 type dielectric ceramic with high dielectric constant

    CN110483034A

  • Dielectric ceramic material with high temperature stability

    CN112723881A

  • High-dielectric-constant NP0 type dielectric ceramic material as well as preparation method and application thereof

    CN119263814A

  • Method of producing low temperature firing dielectric ceramic composition

    EP0534801A1